The development of an integrated participatory framework for the early selection of sustainability indicators for neighborhood sustainability assessment tools: an African perspective - Dawodu, Ayotunde (2019)
Neighborhood sustainability assessment tools (NSATs) have been one of the most important tools for gauging and assessing sustainability practices on an urban scale. It is also the modern day tool used to mitigate undesirable changes due to urbanization while systematically and simultaneously improving communities or cities environmental, economic and social well-being. From the early 2000s till date, several tools have been developed in different regions of the world. The initial set of tools came from more industrialized parts of the words with tools such as BREEAM Communities - UK, LEED Neighborhood Development - US and CASBEE Urban Development - Japan. Slowly, less industrialized countries have followed suite, with tools such as Green Building Index- Malaysia, Green Township-India and BERDE Clustered Development - Philippines. Yet closer inspection showed that no such NSAT exists in the region of Africa. This observation was quite astounding based of the current situation in Africa, which include but not limited to rapid urbanization, severe impact of climate change such as droughts and floods, limited water access, lack of energy access, economic poverty, institutional failures in governance and planning, archaic or draconian technologies and infrastructure etc. These issues are heavily prevalent in African nations and yet it is baffling that no NSAT has been developed for countries within this region, especially since they stand the chance to gain immensely from the NSAT initiative, if applied properly. Further investigation also showed that these tools were not without their flaws and were not as effective as presumed to be. Some of these flaws include their overly environmental focus, the subjective nature of the point based system which NSATs have all come to adopt, their overly top-down method in indicator selection etc.